Current Trends in Biomaterial Utilization for Cardiopulmonary System Regeneration - Adegbenro Omotuyi John Fakoya; David Adeiza Otohinoyi; Joshua Yusuf (Stem Cells International)
The cardiopulmonary system is made up of the heart and the lungs, with the core function of one complementing the other. The unimpeded and optimal cycling of blood between these two systems is pivotal to the overall function of the entire human body. Although the function of the cardiopulmonary system appears uncomplicated, the tissues that make up this system are undoubtedly complex. Hence, damage to this system is undesirable as its capacity to self-regenerate is quite limited. The surge in the incidence and prevalence of cardiopulmonary diseases has reached a critical state for a top-notch response as it currently tops the mortality table. Several therapies currently being utilized can only sustain chronically ailing patients for a short period while they are awaiting a possible transplant, which is also not devoid of complications. Regenerative therapeutic techniques now appear to be a potential approach to solve this conundrum posed by these poorly self-regenerating tissues. Stem cell therapy alone appears not to be sufficient to provide the desired tissue regeneration and hence the drive for biomaterials that can support its transplantation and translation, providing not only physical support to seeded cells but also chemical and physiological cues to the cells to facilitate tissue regeneration. The cardiac and pulmonary systems, although literarily seen as just being functionally and spatially cooperative, as shown by their diverse and dissimilar adult cellular and tissue composition has been proven to share some common embryological codevelopment. However, necessitating their consideration for separate review is the immense adult architectural difference in these systems. This review also looks at details on new biological and synthetic biomaterials, tissue engineering, nanotechnology, and organ decellularization for cardiopulmonary regenerative therapies.